Enhancing TCP Performance in Mobile Ad Hoc Network Using Explicit Link Failure Notification (ELFN) - Alabaedy, Raaid N. (2012)
The dynamics and the unpredictable behaviour of a wireless mobile ad hoc network results in the hindrance of providing adequate reliability to network connections. Frequent route changes in the network relatively introduce incessant link failures which eventually degrade TCP performance considerably. In this research, we are going to study the potential improvement of TCP performance when Explicit Link Failure Notification is implemented as opposed to the standard TCP mechanism. ELFN modifies the ‘slow start’ mechanism that is used in standard TCP so that the throughput achieved from the network can be maximized.